2014
DOI: 10.1111/ped.12396
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic exposure increases maternal but not cord serum IgG in Bangladesh

Abstract: Maternal As exposure was positively associated with IgGmat but not IgGcord . Elevated IgGmat may have implications as regards maternal morbidity and the placental transfer of specific IgGs. Further studies are required to better understand how As may affect maternal and child health by modifying the humoral immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(73 reference statements)
0
11
1
Order By: Relevance
“…A case-control study nested within a prospective cohort in Bangladesh also observed that arsenic exposure potentially modulates humoral immunity regarding viral infection, as higher urinary arsenic was associated with increased susceptibility to hepatitis E viral infection among pregnant women [74]. In contrast to our results, multiple studies have observed positive associations between arsenic exposure and antibody profiles [11,12,75,76]. A small cohort study in Bangladesh (n = 60) found that following booster vaccination, children living within a high W-As area had higher diphtheria and tetanus vaccine-related antibody concentrations, but lower blood counts, compared to children living in a low W-As area [12].…”
Section: Discussioncontrasting
confidence: 89%
“…A case-control study nested within a prospective cohort in Bangladesh also observed that arsenic exposure potentially modulates humoral immunity regarding viral infection, as higher urinary arsenic was associated with increased susceptibility to hepatitis E viral infection among pregnant women [74]. In contrast to our results, multiple studies have observed positive associations between arsenic exposure and antibody profiles [11,12,75,76]. A small cohort study in Bangladesh (n = 60) found that following booster vaccination, children living within a high W-As area had higher diphtheria and tetanus vaccine-related antibody concentrations, but lower blood counts, compared to children living in a low W-As area [12].…”
Section: Discussioncontrasting
confidence: 89%
“…64 However, for 1-day-old chickens who were administered metalloid As for up to 60 days in drinking water, the response to Ranikhet disease virus vaccination (administered on days 1 and 60) was suppressed compared with the control group. 52 Considering the ability of As exposure to suppress cell-mediated immune function, it is possible that early-life exposure to As would adversely affect humoral function in offspring.…”
Section: Persistent Organicmentioning
confidence: 96%
“…In this study their IgG titers were elevated compared to nonexposed pregnant women from a different region. The study suggest that a higher titer of IgG can increase the pregnant women mortality, however, the overall effect on humoral response that these elevation in IgG can have is still unknown [187].…”
Section: Immunotoxicity Of Metalsmentioning
confidence: 99%